Allergy and Its Predictive Factors in the PSAU students-Alkharj City, Saudi Arabia - Alshammary, Amal; Abdo, Seba; AlMutairi, Talal; AlSubaie, Sultan; AlKhald, Abdulmajeed; AlAnazi, Omar; Badawood, Abdullah; AlAnazi, Meshari; Alghamdi, Suad; Alsofyani, Abeer; et al. (International Journal of Innovative Research in Medical Science, 2024)
Background: Allergy is a widespread universal public health challenge that can result in serious complications. The incidences of allergy are continuously on the rise resulting in morbidity and mortality in all age groups. Thus, a clear knowledge of the prevalence of the spectrum of allergic diseases and the accurate identification of environmental triggers is crucial. Aim: The current study was conducted to determine the prevalence, types, risk factors of allergic disorders among students of Prince Sattam bin Abdulaziz University (PSAU) Saudi Arabia. This study may provide useful information for development of a strategic public health plan for optimal management of allergies. Methods: In this cross-sectional study, students were surveyed by an electronic questionnaires and results were analysed and compared. Five hundred adult students (330 males, 170 females) belonging to various colleges at PSAU, participated in this study. Results: Analysis of data from the self-administered questionnaire show that 59% of participants suffered from some type of allergy. The most prevalent type of allergy among participants was of respiratory tract (41%), followed by skin allergy (36%), Gastrointestinal tract (GIT)allergy (14%) and least number of cases were of eye allergy (9%). Fifty five percent cases of allergies were due to environmental triggers, 35% were food allergy, and 10% were animal allergy cases. For food allergy, the most common (59%) allergens were fruits, nuts and vegetables, 26% cases were of fish allergy, 10% of cases were of allergy to milk and the least number of cases (5%) were of allergy to wheat. Conclusion: The prevalence of allergies is high in PSAU and students. Adequate measures should be taken to reduce and manage the rising prevalence of allergies before the problem escalates any further.